Synthesis of the aglycon of scorzodihydrostilbenes B and D - Weimann, Katja; Braun, Manfred (Beilstein Journal of Organic Chemistry, 2019)
Benzyl- and methyl-protected 2,4-dihydroxyacetophenones are added under ruthenium catalysis to 4-methoxy- and 3,4-dimethoxystyrene in a completely regioselective manner. Thus, oxygenated dihydrostilbenes are obtained that feature the skeleton of scorzodihydrostilbenes – antioxidative agents that were recently isolated from Scorzonera radiata. Selective deprotection liberates the corresponding phenols, among them the aglycon of scorzodihydrostilbenes B and D.
Keywords: C–H activation; hydroarylation; phenols; regioselectivity; ruthenium